The Influence of Social Media Marketing and Customer Engagement on Brand Awareness Through the Perspective of Multi-Platform Followers of Baraja Coffee Cirebon - Gina Caesya Anugrah; Muhammad Santoso; Soesanty Maulany (Jurnal Maksipreneur, 2026)
This study examines how social media marketing and customer engagement affect brand awareness among Baraja Coffee’s Instagram and TikTok followers in Cirebon. The study was motivated by the growing importance of digital platforms for local coffee shops in building brand visibility and maintaining relevance in a competitive market. A quantitative explanatory approach was employed, using an online questionnaire distributed to followers of Baraja Coffee’s social media accounts. A total of 394 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The results show that social media marketing has a positive and significant effect on brand awareness, and that customer engagement also has a positive and significant effect on brand awareness. Social media marketing emerged as the stronger predictor, while both variables jointly explained a substantial proportion of the variance in brand awareness. These findings imply that local coffee shops need not only consistent and attractive social media content but also active follower engagement to strengthen brand recognition and recall in digital environments.